the Ethnoecological Study of Local Community Food in Supporting the Development of Culinary Ecotourism in the Sekotong Region, West Lombok - Immy Suci Rohyani; Ahmad Jupri; Supardiono Supardiono; Hilman Ahyadi; Isrowati; Reda; Kurniawan Adi Saputra (Postgraduate, University of Mataram, 2024)
Combining the concept of ecotourism with culinary delights based on local food resources in coastal communities in West Lombok district is one form of appropriate development strategy that will make the West Lombok district region have its own development characteristics leading to sustainable tourism and tourism support which will become the concept of future tourism development. This research examines in more depth the ethnoecological aspects of coastal communities, especially regarding local food. Through this research, data will be obtained regarding the diversity of local food types in coastal communities, mapping community wisdom in processing and utilizing local food. Local community interactions and perceptions of local food diversity. The type of research used is descriptive exploratory with research techniques in the form of exploration. The sampling techniques used in the research were purpose sampling and snowball sampling. Research data collection uses several techniques, including random observation to obtain qualitative and quantitative data on local food typical of the island of Lombok, which uses an open questionnaire targeting local communities according to predetermined criteria. The research results show that coastal communities have more food resources originating from marine resources, both fish and non-fish, these food resources are still protected because most people still harvest the results using simple equipment. There are around 11 types of processed food as a family practice. Tuna fish has the highest ICS (Index of Cultural Significance) value while mackerel fish has the highest variety of uses. Shrimp is the fish group that has the highest ICS value, while cassava leaves have the highest ICS value for the vegetable group. The local wisdom of the community which originates from their ancestors in order to protect their environmental resources is still maintained today.